Exploring Student Perspectives on Spotify Application in Enhancing Listening Skills: A Case Study in an Indonesian Islamic Junior High School - Arra’fu, Muhammad Rafif; Dabamona, Miftahulfadlik; Idrus, Misnariah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
English language learning in Papua, Indonesia, presents a unique context where English is treated as a second language under the Special Autonomy framework. Listening is a fundamental skill in language acquisition, and recent technological developments offer new opportunities to support this process. This study explores students’ perceptions of using Spotify as a digital tool to enhance their English listening skills. Employing a qualitative approach, data were collected through observation and structured interviews with eighth-grade students at a junior high school in Sorong, West Papua. The research subject was chosen to students’ who use the Spotify App, then they will be interviewed regarding their daily use of the Spotify application in enhancing listening skills.  There were 7 students interviewed out of 20 students observed and this research was conducted for 1 month. Findings indicate that students perceive Spotify, particularly its music and podcast features, as an engaging and effective medium for learning. Participants reported improved vocabulary, comprehension, and motivation, highlighting the platform’s accessibility and audio-visual features as beneficial for language exposure. The study concludes that Spotify can serve as a supportive tool for developing listening skills in EFL contexts. It recommends integrating such digital platforms into language instruction, particularly in regions where English holds a special educational role.